High dose methotrexate in the treatment of children with acute lymphoblastic leukemia - Johannes Bondan Lukito (Indonesian Pediatric Society Publishing House, 2007)
Background It has been claimed that around 70% of childhood acute lymphoblastic leukemia (ALL) can be cured. One of the important role is high dose methotrexate (HDMTX) administration during the consolidation therapy. Objective To determine the safety and effectiveness of HDMTX in children with ALL. Methods We reviewed patients with ALL in Pantai Indah Kapuk Hospital, Jakarta during the period August 2000 through July 2005 with observation time run through September 2006. Only patients with normal kidney function were allowed to have HDMTX. Besides good hydration and alkalinization, patients were supported with good hygiene (mouth, skin and anal area). MTX was given in loading dose of 10% from the total dose in ½ hour and the rest 23½ hours for 90%. Leucovorin rescue was started 12 hours after discontinuation of 24 hour MTX IV infusion. Leucovorin was given until the MTX concentration reached 0.1 uM/L. Patients were stratified to low, intermediate and high risk groups; 2 gram/m 2 was given to low risk group and 5 gram/m2 to intermediate and high risk groups. Results There were 20 patients eligible for study. All methotrexate steady-state plasma concentrations (MTX Cp ss ) were above 16 uM/ L, and steady state concentration in CSF was always below 0.5 uM/ L for 2 gram/m 2 and above 0.5 uM/L for 5 gram/m 2 doses. All 20 cases went through the procedure with only mild side effects i. e, mild mucositis, anal furuncle and diarrhea, which recovered 2 weeks later. Only 1 high risk case with initial WBC 612X10 9 /L, succumbed after he went through the HDMTX program smoothly and relapsed subsequently during reinduction phase. Conclusion HDMTX can be given safely to ALL patients with normal kidney function with good supportive care. Five gram/m 2 HDMTX effectively treat the minor disease and/or prevent CNS and testicular leukemia. This study has also given an impression that HDMTX may increase event-free survival.